Grabando historia - Hernández, Alejandra Fabiana; Puig Chouhy, Daya; Avila, Lucía; Pereyra, Guillermo; Lafuente, Agustín; Lizasu, Oliver; Maldonado, Sol Malena; Piturro, Sabrina; Cruz, María Celeste; Montemerlo, Giael; Soria, Florencia; Marioni, Julieta; et al. (Cátedra de Grabado I. Departamento de Artes Visuales. Facultad de Artes, UNC, 2024)
Fil: Hernández, Alejandra Fabiana. Universidad Nacional de Córdoba. Facultad de Artes. Departamento Académico de Artes Visuales; Argentina.